PERTUSSIS INFECTION AMIDST ANTIGENIC DRIFTING OF BORDETELLA PERTUSSIS - I.V. Babachenko (Voprosy Sovremennoj Pediatrii, 2006)
The article deals with the data, which manifests the change in the serotypes of Bordetella рertussis in St. Petersburg, as well as dynamics of biological properties of the causative agent within 1990–2004. The researchers have described the dynamics of dominating serotype changes among the hospital patients from 1.2.3. between 1990–2000 Up to 1.0.3. between 2002–2004, as well as gradual change of chromosomal d na of Bordetellae from iii to iv and pertaktin (PRN) from 1 to type 2 (antigenic drifting). Analysis of the clinical picture and treatment of the disease among 138 children, suffering from pertussis, producing strains of Bordetella рertussis of serotypes 1.2.3. and 1.2.0. (93 people) along with Bordetella рertussis of serotypes 1.0.3 (45 people) showed that biological strain mutability of Bordetella рertussis causes changes in severity and clinical course of pertussis infection, without effecting the clinicial picture of the disease. Strains of pertussis bacilla of serotypes 1.0.3., iv (during electrophoresis in pulsating gel efppbgroup, prn 2 are associated with rarer development of the severe illness forms (by 2.5 times), as well as specific complications (breathbholding and pertussis encephalopathy). The patients had no life threatening complications (respiratory standstill and convulsive disorder).Key words: pertussis, children, antigenic drifting of Bordetella рertussis, biological strain mutability, specific complications of pertussis.